BISPHOSPHONATE INDUCED OSTEONECROSIS OF THE JAWS AND CURRENT THERAPIES - Damla Torul; Mehmet Cihan Bereket (Cumhuriyet University, 2017)
Bisphosphonates are pharmacological agents which are the potent inhibitors of osteoclastic activity. Nowadays, bisphosphonates are used to treat a variety of bone disease or related complications such as metastatic or osteolytic bone disease, hypercalcemia of malignant origin and osteoporosis. Although, bisphosphonates are significantly reduces the skeletal complications of these diseases, they are inevitably cause a specific osteonecrosis characterized by treatment resistant exposed necrotic bone, especially seen in the jaw bones where the bone turnover is high. Currently there is no definitive treatment for this complication induced by the use of bisphosphonates. The search for new treatments methods to prevent the complications that cause patients to become a victim of the economic and social aspects of this situation is still ongoing. This review is intended to provide information about the chemical structure of bisphosphonates, their mechanisms of action and current diagnosis/treatment methods of the osteonecrosis.